Proceedings of the 2014 Annual Conference on Genetic and Evolutionary Computation 2014
DOI: 10.1145/2576768.2598240
|View full text |Cite
|
Sign up to set email alerts
|

Minimal walsh structure and ordinal linkage of monotonicity-invariant function classes on bit strings

Abstract: CopyrightItems in 'OpenAIR@RGU', Robert Gordon University Open Access Institutional Repository, are protected by copyright and intellectual property law. If you believe that any material held in 'OpenAIR@RGU' infringes copyright, please contact openair-help@rgu.ac.uk with details. The item will be removed from the repository while the claim is investigated. ABSTRACTProblem structure, or linkage, refers to the interaction between variables in a black-box fitness function. Discovering structure is a feature of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…More complex algorithms will operate on the representation in more complex ways and the concept of coherence will need to be generalised. One current line of active research [1,2] is to use probabilistic graphical models on representation space to structure fitness in ways coherent with the action of algorithm operators.…”
Section: Discussionmentioning
confidence: 99%
“…More complex algorithms will operate on the representation in more complex ways and the concept of coherence will need to be generalised. One current line of active research [1,2] is to use probabilistic graphical models on representation space to structure fitness in ways coherent with the action of algorithm operators.…”
Section: Discussionmentioning
confidence: 99%
“…In [1] it was shown that a column vector of Walsh coefficients could be computed using the Hadamard matrix. The constant term α ∅ is never necessary to maintain the ordering of function values as it is added to every output.…”
Section: Walsh Structuresmentioning
confidence: 99%
“…We adopt the convention used in [1] and write for the function class of f : C f = [r 1 , r 2 , ..., r 2 n ] where r i is the rank of the ith solution. (The solutions are ordered as binary integers.)…”
Section: Walsh Structuresmentioning
confidence: 99%
See 2 more Smart Citations